Comparing the Genetic Parameters of Three Rice Varieties on Suboptimal Land Using the SRI Method - Rozen, Nalwida; Kasim, Musliar; Dwipa, Indra; Hervani, Dini (Department of Agronomy and Horticulture, IPB University, 2022)
The conversion of fertile land into industrial areas and construction development has contributed to the decline of rice production in Indonesia. Therefore, it is necessary to expand the rice fields to the sub-optimal land, i.e. lands with high levels of Fe and Al and low soil pH. One of the solutions that can potentially solve the problem is choosing varieties of rice that can adapt to the suboptimal land environment; the rice varieties can be obtained by estimating rice genetic parameters and selecting the optimal planting methods. One method that can potentially improve rice yield is “System of Rice Intensification”, or SRI method. Our study was conducted in the rice fields on suboptimal land at Pasar Ambacang, Kuranji District, Padang, Sumatra, from December 2019 to April 2020. The aims of the experiment are to determine the genetic parameters and responses of the three rice varieties to suboptimal land using the SRI method. A complete randomized design with four replications was used to set up the experiment using three varieties of rice, i.e. “Batang Piaman”, “Bujang Marantau”, and “IPB3S”. Based on the plant growth measurement and analysis of the genetic parameters, we found that the plant growth characters, particularly height and panicles length, had high heritability and genetic progression values.